Clear as mud? web-based accountability in the Malaysian Non-Profit Organizations (NPOs) - Mahamud, Mohd Hisham; Wan Mohamad Noor, Wan Nurul Basirah; Abd Razak, Siti Noor Azmawaty (Universiti Teknologi MARA, Kedah, 2024)
In the realm of non-profit organizations (NPOs), maintaining transparency and demonstrating responsible funds management is crucial for establishing trust and accountability with stakeholders. The study investigates the extent to which Malaysian non-profit organizations (NPOs) used their websites to demonstrate accountability towards their stakeholders. Upon analyzing the annual reports of 30 NPOs, the study revealed that while a substantial proportion (67%) disclosed information across multiple accountability domains. However, the depth and breadth of disclosure varied significantly. These findings suggest a selective approach to transparency, potentially at odds with theoretical expectations of comprehensive information sharing. Moreover, a comparison with public sector practices highlights the prioritization of strategic and fiduciary accountability over financial and procedural aspects. This research contributes to the understanding of accountability challenges faced by Malaysian NPOs and provides implications for enhancing organizational transparency and public trust.